Hot Tea Drinking and the Risk of Esophageal Cancer: A Systematic Review and Meta-Analysis. (30th June 2022) - Zhong, Yulian; Yang, Chao; Wang, Niannian; Pan, Da; Wang, Shaokang; Sun, Guiju
Abstract: This study aimed to explore the association between hot tea drinking and the risk of esophageal cancer. PubMed, Web of Science, Embase, Scopus and Cochrane library were searched for relevant studies from inception to October 29, 2020 by using (Tea OR "Green Tea" OR "Black Tea") AND ("Esophageal Neoplasms" OR "Esophageal Cancer" OR "Esophagus Cancer") as key words. The Newcastle-Ottawa Scale (NOS) was used to evaluate the quality of the literatures. The meta-analysis was performed using the Revman 5.3 and Stata 13.0 software. The subgroup analyses were conducted on publication year, population regions, tea type, tea temperature, and type of esophageal cancer, and the publication bias was calculated using the funnel plot and Begg's regression. A total of 12 case-control studies with 5253 cases and 8273 controls were included. The meta-analysis displayed that hot tea drinking was significantly associated with the risk of esophageal cancer (pooled odds ratio, 2.04; 95% CI, 1.78–2.31). However, the research evidence is still limited, therefore, it needs further discussion.